A Description of Neonatal Death in the Perinatology Ward of Muhammadiyah Pekajangan Hospital, Pekalongan Regency - Y Yuliati; Neti Mustikawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Neonatal mortality reate is an indicator to determine the community health status involving various programs in the community. Neonatal mortality is defined as death in infants aged 0-28 days caused by maternal and infant factors. Objective: This study aims to describe neonatal mortality in the perinatalogy ward of Muhammadiyah Pekajangan Hospital Pekalongan Regency. Samples: A descriptive study with a longitudinal design was used. The research sample was neonates who died at 0-28 days in the perinatology ward of Muhammadiyah Pekajangan Hospital Pekalongan Regency in the 2017-2020 period as many as 57 documents. Methodes: The sampling technique used was total sampling. The research instrument used medical records. Data analyisis used univariate analysis with frequency distribution. Results: The results of the study showed that the majority of neonatal mortality was 66,7% male, 93,3% aged 0-6 days, 56,1% premature, 43,9% caesarean section and 61,4% low body weight. The cause of neonatal death is known to be 64,9% asphyxia. Conclusion: Recommendations for hospital are to analyze trend in the causes of neonatal deaths to be considered for hospital policy making in providing health services to pregnant and maternity women.